Ludic Experience Using Lean Manufacturing Standard Operating Sheet Tool to Improve the Teaching and Learning of Standardized Work - Tapia Vargas, Flor de María Milagros (2023)
This study proposes the application of a ludic and practical experience, which includes the use of the standard operation sheet tool for the purpose of improving the teaching and learning of standardized work. In this way, the study helps to solve the problem of the communication of standards in companies, and improve the capabilities and competences of Industrial Engineering students.The study is applied and relational. It was aimed at comparing the difference in the assembly cycle time of a pegboard before and after teaching and learning the operation sheet standard, by means of a parametric repeated measures test, in order to verify if the assembly cycle time decreases.The results obtained confirmed the research hypothesis, reduced the variability of communication of the standard and improved the integration of teamwork.